The Effectiveness of the Experimental Method of Control in the Physical Education of Students of Special Medical Groups with Cardiovascular Diseases on the State of Psychophysiological Functions - Koryahin, V. M.; Blavt, O. Z. (Physical Education Theory and Methodology, 2017)
The objective is the dynamics of psychophysiological functions of students of special medical group with cardiovascular diseases under the influence of the experimental control technique in their physical education is carry through analyze. Materials & methods: to solve the research problems, the methods of empirical level: pedagogical experiment, pedagogical testing: methods of testing psychophysiological functions, instrumental methods, methods of mathematical statistics were used. In the experiment, 40 special medical groups student (in equal numbers of girls and boys) participated in the experiment with cardiovascular diseases, which have the character of functional changes, without organic damage to the heart. Results: the study of psychophysiological functions the students in special medical group according to targeted correction of funds by type of diseases, which makes it possible to take into account individual and typological features of the influence of cardiovascular diseases on their dynamics under the influence of physical education, for the first time has been practically realized. A positive dynamics of the state of their psycho-physiological functions the results of the pedagogical experiment on checking the effectiveness of the experimental control methodology in the physical education of students of special medical group with cardiovascular diseases have established. Conclusions: is to use the proposed control methodology, which helps to ensure the effectiveness of physical education of students with cardiovascular diseases it is proved expedient. On the basis of the results of the study, the effectiveness of the purposeful correction of pedagogical influences in the course of physical education on the basis of permanent control was established.